2018
DOI: 10.1257/pandp.20181117
|View full text |Cite
|
Sign up to set email alerts
|

The Changing Face of Debt and Financial Fragility at Older Ages

Abstract: We investigate changes in older individuals' financial fragility as they stand on the verge of retirement. Using data from the Health and Retirement Study (HRS), we compare how debt has changed for successive cohorts of people age 56–61. Our analysis shows that recent older Americans close to retirement hold more debt, and hence face greater financial insecurity, than earlier generations. This is primarily due to having bought more expensive homes with smaller down payments. We discuss possible policy implicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 13 publications
1
44
0
Order By: Relevance
“…Unfortunately, studies find that older Americans have become increasingly more leveraged over time. Lusardi et al (2018) find that the mean debt-toasset ratio among adults ages 56-61 rose from 45 percent for the oldest birth cohort to 104 percent for the youngest cohort, and even the median debt ratio grew from 4 percent to 15 percent between birth cohorts. Butrica and Karamcheva (2018) find that the mean debt-to-asset ratio among adults age 62-69 increased from 10 percent in 1998 to 23 percent in 2014.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Unfortunately, studies find that older Americans have become increasingly more leveraged over time. Lusardi et al (2018) find that the mean debt-toasset ratio among adults ages 56-61 rose from 45 percent for the oldest birth cohort to 104 percent for the youngest cohort, and even the median debt ratio grew from 4 percent to 15 percent between birth cohorts. Butrica and Karamcheva (2018) find that the mean debt-to-asset ratio among adults age 62-69 increased from 10 percent in 1998 to 23 percent in 2014.…”
Section: Introductionmentioning
confidence: 85%
“…Debt at older ages. Recent studies have documented the rise in debt among older Americans (Brown et al 2019;Butrica andKaramcheva 2013, 2018;Butrica and Mudrazija 2016;GAO 2014; Joint Center for Housing Studies of Harvard University 2014; Masnick et al 2006;Karamcheva 2013;Lusardi et al 2018;Munnell et al 2016;Smith et al 2010). Not only are older adults more likely to carry debt, but their level of indebtedness has increased substantially over time.…”
Section: Introductionmentioning
confidence: 99%
“…Research on financial vulnerability has turned increasingly toward discovering the impact of economic shocks on financial stability, with specific emphasis on the importance of emergency savings (Chase, Gjertson, & Collins, ; Gjertson, ; Lusardi, ; McKernan et al, ; Mills & Amick ). Characterized as a lack of liquid assets equal to three months of income, or the inability to come up with $2,000 in 30 days, financial fragility is estimated to impact 39 to 46 percent of all U.S. households (Brooks et al, ; FINRA Investor Education Foundation, ; Lusardi et al, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For some, managing mortgages is difficult and/or they are under water: 10 percent of those with mortgages have been late with mortgage payments at least once in the previous year, and 9 percent of those with mortgages or equity loans reported owing more on their homes than they believe they could sell them for. In Lusardi et al (2018) we showed that those nearing retirement today hold higher mortgage debt than did previous generations.…”
Section: Assessing Near-retirees' Borrowing Behaviorsmentioning
confidence: 82%